TINJAUAN LITERATUR : PEMANFAATAN APLIKASI KESEHATAN DIGITAL SEBAGAI ALTERNATIF LAYANAN KESEHATAN SELAMA MENGHADAPI PANDEMI COVID-19: LITERATURE REVIEW: UTILIZING DIGITAL HEALTH APPLICATIONS AS ALTERNATIVE HEALTH SERVICES DURING THE COVID-19 PANDEMIC - Nur Aji; Dwi Anjani (Jurnal Komunitas Farmasi Nasional, 2023)
The Covid-19 pandemic is a non-natural disaster caused by the SARS-CoV-2 virus which can be transmitted from human to human through coughing/sneezing droplets (droplets), not through the air. People who are most at risk of contracting this disease are people who have close contact with Covid-19 patients, including those caring for Covid-19 patients, so a new strategy is needed that allows for face-to-face health services to reduce the risk of Covid-19 transmission. Digital health is one of the innovations that can be used to deal with this crisis. Therefore, in an effort to improve health services in crisis conditions, this review article will discuss digital health and its use as an effort to improve health services during the Covid-19 pandemic. The method used is a systematic review by looking systematically at journals and articles on Google Scholar, Scopus, and PubMed. As a result, seven journals were obtained that met the criteria regarding the use of digital health as a health service in the era of the Covid-19 pandemic. With the many types of digital health that exist, it allows more optimal utilization for certain conditions and does not rule out the possibility of using digital health in the future because of the large potential, scalability, and benefits presented. So far digital health is a very safe and good solution for alternative health services during the Covid 19 pandemic.